Islamic revivalism, religious freedom and the non-Muslims in Malaysia: a preliminary discussion - Abdullah, Amini Amir (Universiti Putra Malaysia Press, 2003)
The non-Muslims' responses towards the Islamization policy of the government and Islamic revivalism in Malaysia and their major organisation aims regarding non-Muslims affairs have many things in common. From the questionnaires and interviews, it is possible to summarise the responses of the non-Muslims in Malaysia. Although the Malaysian constitution guarantees the non-Muslims religious freedom and rights, what matters are the actual practices of the Malaysian government and civil servants in implementing the constitutional provisions. The non-Muslims are not convinced about their constitutional rights. Generally, their fear are based on the lack of a clear and open discussion. The non-Muslims sense of insecurity will be increased as long as their rights are denied or neglected. Attempts to Islamize Malaysia will further intensify the non-Muslim's feeling of disadvantage and they will react to fight for their rights.